Human behaviour in multimodal interaction: main effects of civic action and interpersonal and problem-solving skills - Makri, Eleni; Spiliotopoulos, Dimitris; Vassilakis, Costas; Margaris, Dionisis (Journal of ambient intelligence and humanized computing, 2020)
Metacognitive skill training may rest within any kind of social interaction that requires awareness of what an individual and others think, in social, educational and organizational settings alike. This work is an extensive study of multimodal application interaction (virtual agent, spoken dialogue, visual communication of progress) for metacognitive skill training via negotiation skill training scenarios. Human behaviour, as effected by civic action and interpersonal and problem-solving skill training, is investigated through interaction sessions with a virtual agent on multimodal multiparty negotiation. This work reports on the results of the user-system evaluation sessions involving 41 participants before and after interaction with the system, integrating macro- (dialogue system performance) and micro- (metacognitive-related and individual- and community-level-related attitudes and skills) factors. Findings indicate significant and positive relationships between user and system evaluation questions after interaction with the dialogue system and between self-efficacy, self-regulation, individual readiness to change, mastery goal orientation, interpersonal and problem-solving skills and civic action before and after the interaction experience. Implications, limitations and further research issues are discussed in light of context of the multimodal interaction and its effects on the human behaviour during metacognitive skill training.